Hybrid connections: Unveiling emotional intelligence’s influence on hybrid work perceptions and job performance - Junça Silva, A.; Damas, H. (The Spanish Journal of Psychology, 2025)
Hybrid work has been the most identified flexible working model to be adopted after the recent pandemic crisis. However, little is known about how and when it may impact job performance. Relying on the Job-Demands-Resources model, we developed a conceptual model testing the indirect effect of perceived effects of hybrid working models on job performance through decreased occupational stress. Furthermore, we also argued that emotional intelligence would play a moderating role in the former indirect relationship. The authors utilized a time-lagged survey approach, gathering data from 1055 hybrid workers employed at diverse financial organizations in Portugal across three distinct time points (T1, T2, T3). Quantitative analysis of the data was conducted using the SPSS PROCESS Macro and JASP software. The findings showed that a positive attitude toward hybrid work positively influenced job performance once it decreased employees’ occupational stress. This relationship was stronger for those who scored higher on emotional intelligence (versus lower scores). The findings enhance our comprehension of emotional intelligence’s significance within the nexus of hybrid work perception, performance, and stress. They underscore the pivotal role of fostering emotional intelligence as a fundamental component of hybrid work management strategies aimed at enhancing both employee well-being and performance in flexible working settings.